RESOLUSI PERSERIKATAN BANGSA-BANGSA (PBB) DALAM KONFLIK INTERNAL DI LIBYA PADA TAHUN 2011-2020 - Rohayu "; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Indonesia is a tropical country as the fourth biggest chili producer in the world. It suffered from chili supplies in 2015 that required to import that good. There were pros and cons between local chili producers and the consumers. This research decribed Indonesian small and middle farmers’ responses to the policy of chili import from India.                              This research is descriptive qualitative. To describe responses from the small and middle local farmers, I did secondary data collection techniques by analyzing document from books, Indonesian official governement’sreports, journals, publications, websites, and various scientific articles that are relevant to solve the issue. Detailed analyisis is supported by nation-state level with perspective of liberalism.                              The result showed that chili import from India led to protests from chili farmers since they suffered financially and socially. Indonesian government should have mitigated this situation by protecting them. The lack of officials support has resulted in decreasing number of farmers growing chili and worse import measures.   Key Words: Import, chili, Indonesian chilli farmers, India